Etika Pencegahan Asusila dalam Tafsir Surah An-Nur Ayat 30–31: Studi Komparatif Tafsir Al-Misbah dan Al-Maraghi - Siregar, Fahmi Randa; Pulungan, Khoirul Falah; Zein, Achyar; Astuti, Rahayu Fuji (Medan Resource Center, 2025)
Humans are inherently social beings, living in communities comprised of both men and women. In such social settings, various social issues, including immorality, often emerge. According to data from the Indonesian Ministry of Women’s Empowerment and Child Protection, there have been 9,584 reported cases of immoral behavior, with 1,963 male victims and 8,187 female victims. This alarming issue requires a comprehensive and contextually grounded solution. One such solution lies in the application of the moral and ethical teachings found in Surah An-Nur verses 30–31 of the Qur’an. This study aims to explore and describe the moral values embedded in these verses, as interpreted through two distinct tafsir approaches: the classical interpretation of Tafsir Al-Maraghi and the contemporary perspective of Tafsir Al-Misbah. The novelty of this study lies in its comparative approach, bridging traditional and modern interpretations to uncover a holistic understanding that addresses present-day moral challenges in Indonesia. Employing a descriptive qualitative methodology within the framework of library research, this study analyzes and compares the aforementioned tafsir works. The findings indicate that the values conveyed in Surah An-Nur verses 30–31—such as the importance of lowering one's gaze (ghaddul bashar), maintaining modesty, and fostering mutual respect between genders—remain highly relevant in efforts to prevent immoral behavior in Indonesian society. By internalizing and implementing these Qur'anic values, it is possible to cultivate a generation that excels not only in knowledge and skills but also in strong moral character. Such individuals will be better equipped to resist immoral influences, face global challenges, and make positive contributions to the nation and the wider world.